Geochemical evaluation of Pabdeh Formation in Nosrat field, southeast Persian Gulf using Rock- Eval VI pyrolysis - Biuk ghorbani; Reza ghavami riabi; Mohammad reza kamali; mohammad sadeghi (Journal of Stratigraphy and Sedimentology Researches, 2015)
The present study was performed on 59 drillhole cuttings from Pabdeh Formation in Nosrat oil field using Rock- Eval VI pryrolysis. Geochemical analysis indicated that Pabdeh Formation possesses poor to good hydrocarbon potential. Plotting S1 against TOC suggests that samples were not affected by polluting substances such as crude oil and lubricants while drilling operation. Jones organic fancies diagram shows B-BC area indicating that Pabdeh Formation was deposited in marine anoxic to oxic environments. HI vesus Tmax shows that most samples initially have had type II kerogen and now reflecting a mixture of type II to III kerogen (capable of generating oil) that have already entered oil generation window. In addition, S1+S2 versus TOC plot also suggests that Pabdeh Formation can be considered as a capable hydrocarbon generating source rock in the study area.